ATP Signaling Controlling Dyskinesia Through P2X7 Receptors - Fonteles, Analu A.; Neves, Julliana C. S.; Menezes, Ana Paula F.; Pereira, Juliana F.; Silva, Ana Thais A.; Cunha, Rodrigo A.; Andrade, Geanne M. (Frontiers in Molecular Neuroscience, 2020)
Dopamine replacement therapy with L-DOPA (L-3,4-dihydroxyphenilalanine) is the only temporary therapy for Parkinson’s disease but it triggers dyskinesia over time. Since increased neuronal firing bolsters purinergic signaling, we now tested if the selective and blood brain barrier-permeable P2X7 receptor antagonist Brillant Blue-G (BBG, 22.5-45 mg/kg intra-peritoneally) attenuated behavioral, neurochemical and biochemical alterations in rats turned hemiparkinsonic upon unilateral striatal injection of 6-hydroxydopamine (6-OHDA) and treated daily with L-DOPA (30 mg/kg by gavage for 22 days). Blockade of P2X7 receptors decreased L-DOPA-induced dyskinesia and motor incoordination in hemiparkinsonian rats. In parallel, BBG treatment rebalanced the altered dopamine D1 and D2 receptor density and signaling as well as neuroinflammation in the striatum and substantia nigra. These findings herald a hitherto unrecognized role for purinergic signaling in the ethiopathology of dyskinesia and prompts P2X7 receptor antagonists as novel candidate anti-dyskinesia drugs.